2022
DOI: 10.21037/atm-22-517
|View full text |Cite
|
Sign up to set email alerts
|

IKKα contributes to ischemia-induced autophagy after acute cerebral ischemic injury

Abstract: Background: The function of IκB kinase α (IKKα) in the brain is largely unknown. This study examined the effects of IKKα on autophagy after cerebral ischemia.Methods: Permanent distal middle cerebral artery occlusion (dMCAO) was conducted in C57/BL6 mice.Oxygen-glucose deprivation/reperfusion (OGD/R) was performed to mimic ischemia injury in neuro-2A (N2A) cells in vitro. Autophagy activation was assessed by detecting the ratio of microtubule-associated protein 1 light chain 3β (LC3B)-II/LC3B-I and Cyto-ID aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Bay 11-7082, an inhibitor of the NF-κB pathway, downregulated the autophagy-related proteins except p62 and decreased the size and number of autophagosomes, based on the analysis of monodansylcadaverine staining and transmission electron microscope observation. Similarly, there is evidence that IKK/NF-κB directly enhances autophagy by inducing the expression of related proteins such as ATG5, LC3, and Beclin1 [ 23 , 50 ]. These results demonstrate that SR attenuates osteoclastogenesis by inhibiting autophagy through the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bay 11-7082, an inhibitor of the NF-κB pathway, downregulated the autophagy-related proteins except p62 and decreased the size and number of autophagosomes, based on the analysis of monodansylcadaverine staining and transmission electron microscope observation. Similarly, there is evidence that IKK/NF-κB directly enhances autophagy by inducing the expression of related proteins such as ATG5, LC3, and Beclin1 [ 23 , 50 ]. These results demonstrate that SR attenuates osteoclastogenesis by inhibiting autophagy through the NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that the NF-κB pathway can directly enhance autophagy by inducing the expression of autophagy-related proteins, such as autophagy-related 5 homolog (ATG5), microtubule-associated protein light chain 3 (LC3), and Beclin1. These proteins are reported to be highly involved in osteoclast activity, including the formation of a ruffled border, the transport of lysosomes, and the release of protease in vitro and in vivo [ 21 , 22 , 23 , 24 ]. Nevertheless, the role of the NF-κB pathway and autophagy in the mechanism of osteoclastogenesis inhibited by SR has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…TUNEL staining was implemented with the In Situ Cell Death Detection Kit following the manufacturer's requirements (KeyGEN, China). The mouse retinal tissue sections were then stained with DAPI (a nuclear-specific marker), and captured with a confocal microscope (Zeiss) to analyze the apoptosis in the retinal tissues of each group of mice [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the early stage of Frontiers in Pharmacology frontiersin.org autophagosome formation, Beclin-1 binds to Vps34 to form a type III PI3K complex and then, together with Atg1 and Atg9, regulates phagosome formation (Song et al, 2021). LC3 is cleaved by Atg4 protease to form LC3-I, which then couples with phosphatidylethanolamine to form LC3-II, which attaches to the surface of the autophagic vesicle (Dong et al, 2022). p62 can bind to ubiquitin substrates and LC3, which are integrated into autophagosomes by binding to LC3-II and finally degrade autophagic lysosomes (Jeon et al, 2021).…”
Section: Electroacupuncture Treatment For Weight Reduction May Be Clo...mentioning
confidence: 99%